Management of auricular transcutaneous neuromodulation and electro-acupuncture of the vagus nerve for chronic migraine: a systematic review - Fernández-Hernando, David; Fernández-de-las-Peñas, Cesar; Pareja-Grande, Juan A.; García-Esteo, Francisco J.; Mesa-Jiménez, Juan A. (Frontiers in Neuroscience, 2023)
Background: Migraine is a primary headache accounting for associated symptoms, such as nausea, vomiting, or sensitivity to light and sound. Objective: The aim of this study was to conduct a systematic review on the effectiveness of non-invasive neuromodulation, auricular transcutaneous vagus nerve stimulation (at-VNS), and electro-ear acupuncture of the vagus nerve in patients with migraine headaches. Methods: Six databases were searched from inception to 15 June 2022 for clinical trials, in which at least one group received any form of non-invasive neuromodulation of the vagus nerve for managing migraine with outcomes collected on pain intensity and related disability. Data regarding the participants, interventions, blinding strategy, outcomes, and results were extracted by two reviewers. The methodological quality was assessed with the PEDro scale, ROB, and Oxford scale. Results: The search identified 1117 publications with 9 trials eligible for inclusion in the review. The methodological quality scores ranged from 6 to 8 (mean: 7.3, SD: 0.8) points. Low-quality evidence suggests some positive clinical effects for the treatment of chronic migraine with 1Hz with at-VNS and ear-electro-acupuncture compared with the control group at post-treatment. Six of the studies provided evidence with fMRI the relationship between chronic migraine and a possible positive effect as a treatment with at-VNS and the neurophysiological effects. The pain intensity, migraine attacks, frequency, and duration were measured by three of them with positive results at post-treatment. And only the 7% reported adverse events using at-VNS. All studies reported the results at post-treatment period in their respective main outcomes. And all studies with fMRI provided strong evidence of the relationship between Locus Coeruleus, Frontal Cortex and other superior brain areas with the auricular branch of the Vagus nerve with at-VNS. Conclusion: Some positive effects regarding the effect of non-invasive neuromodulation, auricular transcutaneous vagus nerve stimulation (at-VNS), and electro-ear acupuncture of the vagus nerve on migraine are evident based on the current literature, but there are not enough data to obtain strong conclusions.